WIDOWER'S AGE AND NUMBER OF CHILDREN AFFECT PARENTING STYLE AND REMARRIAGE DECISION - Frisilia Octaviana Yolanda; Hermanto Tri Joewono; Dwi Aprilawati (Majalah Biomorfologi, 2022)
Highlight:1. The widow will outsource childcare to other people, such as the widow's mother, stepmother, aunt, or other relatives who believe they know more about childcare after the wife's death.3. There was a significant relationship between widower's age and the number of children affecting parenting style and remarriage decision.Abstract:Background: The high maternal mortality ratio automatically represents the highest number of widowers in Indonesia. The change of status from a husband to a widower does not rule out the possibility of being able to change his role and function in the family. Objective: To describe that the widower's age and the number of children have an impact on the parenting style and the desire to remarry. Materials and Methods: This study was an observational study with a cross-sectional design. Husbands who had been left by their wives for two years or more owing to maternal death and had one or more children before the wife's maternal death were the subjects of this study. Widower's age, as well as kid's parenting patterns before the death of the mother were recorded. This study was likewise subjected to an ethics review and relied on informed consent. Results: Widowers who had one child before their wife's death and decided to remarry accounted for 7 subjects (87.5%), while those who did not remarry accounted for 5 (31.3%). On the association between a widower's age and child-rearing practices, there were two respondents (40%) who chose to entrust their children's care to someone else or not to be cared by themselves. Conclusion: There was a significant relationship between widower's age and the number of children and the parenting style and remarriage decision. Single parents who decided to remarry were single parents at a relatively younger age.